Teacher Agency as Technologies of the Self and as Actionality: Implications for ELT Micro-Centric Policy Making - Setiono Sugiharto (The English Teacher, 2021)
This article critically examines the notion of teacher agency in light of two important conceptual frameworks: technologies of the self and transitionalist-actionistic, or conduct pragmatism. Using the former framework, teacher agency was analyzed in terms of its inherent status and dynamic flux within one’s self, while using the latter it was scrutinized for its transitional-actionistic nature triggered by one’s action or conduct. The article then argues that viewing teacher agency from these two vantage points can contribute to our understanding of the crucial role a teacher can play in creating a micro-centric policy of teaching and learning English in a specific locality, as well as of the enactment of this policy by individual teachers in a classroom setting. Implications for this critical examination of teacher agency include the import of the (re)activation of teacher agency, and its enactment both in the policy-making processes and in the teaching practices.